Follicular helper T‐cells: expanding roles in T‐cell lymphoma and targets for treatment. (12th May 2014) - Ahearne, Matthew J.; Allchin, Rebecca L.; Fox, Christopher P.; Wagner, Simon D.
Summary Follicular helper T‐cells (Tfh cells) are a subset of CD4+ T‐cells that are essential for normal production of high affinity antibodies. Tfh cells characteristically produce IL21 and IL4 and show high expression of surface markers CXCR5, ICOS, PDCD1 (PD‐1) and the chemokine CXCL13. In this review we will focus on the emerging links between Tfh cells and subtypes of T‐cell non‐Hodgkin lymphoma: angioimmunoblastic T‐cell lymphoma (AITL) and ~20% of peripheral T‐cell lymphoma not otherwise specified (PTCL‐NOS) have surface marker features of Tfh cells and share a spectrum of genetic abnormalities. The recurrent genetic abnormalities associated with AITL include mutations in epigenetic modifiers such as TET2 and DNMT3A and the motility and adhesion gene, RHOA, is mutated in up to 70% of cases. ~20% of PTCL‐NOS demonstrate RHOA mutations and have other characteristics suggesting an origin in Tfh cells. The recognition that specific genetic and surface markers are associated with malignant Tfh cells suggests that the next few years will bring major changes in diagnostic and treatment possibilities. For example, antibodies against IL21, PDCD1 and ICOS are already in clinical trials for autoimmune disease or other malignancies and antibodies against CXCL13 are in pre‐clinical development.